Macronutrient Deficiencies in Citrus: Calcium, Magnesium, and Sulfur: SL 202/SS421, 1/2003 - Zekri, Mongi; Obreza, Thomas (EDIS, 2003)
This document is SL 202, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: January 2003. SL 202/SS421: Macronutrient Deficiencies in Citrus: Calcium, Magnesium, and Sulfur (ufl.edu)